2014
DOI: 10.7314/apjcp.2014.15.9.3933
|View full text |Cite
|
Sign up to set email alerts
|

Un-met Supportive Care Needs of Iranian Breast Cancer Patients

Abstract: Background: Assessment of supportive needs is the requirement to plan any supportive care program for cancer patients. There is no evidence about supportive care needs of Iranian breast cancer patients. So, the aims of present study were to investigate this question and s predictive factors. Materials and Methods: A descriptivecorrelational study was conducted, followed by logistic regression analyses. The Supportive Care Needs Survey was completed by 136 breast cancer patients residing in Iran following their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 50 publications
3
50
2
3
Order By: Relevance
“…Results of previous studies also showed that fear of screening is a major breast cancer screening barrier (Bener et al, 2009;Ahangar et al, 2014). However, results of some studies indicate that sometimes fear can be both a barrier and an encouraging and facilitating factor for breast cancer screening (Abdollahzadeh et al, 2014). Therefore to eliminate women's fear and to cause them to participate in screening and to increase screening participation rate, warning women about sequences of late detection of breast cancer and using painless methods, can be effective ways.…”
Section: Discussionmentioning
confidence: 96%
“…Results of previous studies also showed that fear of screening is a major breast cancer screening barrier (Bener et al, 2009;Ahangar et al, 2014). However, results of some studies indicate that sometimes fear can be both a barrier and an encouraging and facilitating factor for breast cancer screening (Abdollahzadeh et al, 2014). Therefore to eliminate women's fear and to cause them to participate in screening and to increase screening participation rate, warning women about sequences of late detection of breast cancer and using painless methods, can be effective ways.…”
Section: Discussionmentioning
confidence: 96%
“…According to Vehling et al (2014) the main cause of cancer patients' perception of lack of dignified care was due to physical related symptoms (Vehling et al, 2014). Faghani et al (2014) showed that Iranian cancer patients experience many physical symptoms such as pain during the survival period (Abdollahzadeh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although advances in current treatments dramatically increase the number of cancer survivors in recent years, fear of recurrence is still a main concern for cancer patients (Kim et al, 2012). The findings of some studies conducted in Iran also indicated fear of recurrence as one of the major concerns among Iranian cancer patients (Taleghani et al, 2006;Abdollahzadeh et al, 2014). It seems fear of recurrence negatively influence patients' perception of dignity.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients have many physical, psychological, social and spiritual needs and require high quality nursing care (Yeh et al, 1999;Abdollahzadeh et al, 2014;Abbasnezhad et al, 2015;Avestan et al, 2015;Fathollahzade et al, 2015). Cancer patients are very dependent on their caregivers and the low level of consciousness among nurses may leads to negative many negative consequences in them (Hsiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%